Answer:
Point Form:
(0,4)
Equation Form:
x=0,y=4
Step-by-step explanation:
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Answer:
The desired equation is y = (-8/3)x + 26/3.
Step-by-step explanation:
Moving from (1,6) to (4, -2) involves an increase of 3 in x and a decrease of 8 in y. Thus, the slope of the line thru these two points is m = rise / run = -8/3.
Using the slope-intercept form of the eq'n of a straight line and inserting the data given (slope = m = -8/3, x = 4, y = -2), we get:
y = mx + b => -2 = (-8/3)(4) + b, or -2 = -32/3 + b
Multiply all terms by 3 to clear out the fraction:
-6 = -32 + 3b.
Then 26 = 3b, and b = 26/3.
The desired equation is y = (-8/3)x + 26/3.
Answer:
Since both terms are perfect squares, factor using the difference of squares formula,
a2−b2=(a+b)(a−b) where a=x and b=16.(+)x16)
Step-by-step explanation: